PRAKTEK RIBA SALAH SATU PENYEBAB KEMISKINAN MASYARAKAT (Studi Kasus di Kecamatan Wates, Kebupaten Kulon Progo) - Supardjijo Supardjijo (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2014)
Matter of life and life are two things that can not be avoided existence. Human life requires resources in order to live a decent life in a community environment. Source of life is important to maintain that human life can exist in society at large are looking for a loan of practice arrived. Venture capital lending practices beginning Rp500.000,00 usury. At first it appeared a glimmer of hope for the poor and they will be able to continue its trading business. Research conducted usury is the practice of Riba Qardh. The results of the analysis found a few things: (a) Receipt of loan capital reduced by 10% for administrative costs and loan principal bears interest at 10% which is 11 times the weekly installments installments (77 days); (b) The rate of interest based on the amount of the loan at 46.75% per year; (c) the amount of the real interest rate borrowings amounted to 105.34% per year; (d) Calculation of gross profit mathematics 20% per day after 77 days has its own capital of Rp 2,140,000.00; (e) Calculation of mathematics gross profit of 19% per day after 77 days has its own capital of Rp 1,761,500.00; (f) Calculation of gross profit mathematics 18% per day after 77 days has its own capital of Rp 1,377,600.00; (g) a mathematical calculation of gross profit of 17% per day after 77 days has its own capital of Rp 1,377,600.00; (h) the mathematical calculation of gross profit of 16% per day in week 1 loan of Rp 413,600.00, while the loan debt is USD 500,000.00; (i) The impact on the general public about the borrower is never out of dependence on the practice of usury Key words : loyal customers, the poor, usury